Directions(1-10): Comparing I and II and select a required option.
- I.x^2 + 2x – 63 = 0
II.y^2 – 15y + 56 = 0No relation.y>xx>yy>=xx>=yOption D
I.x^2 + 2x – 63 = 0
=>x^2 + 9x – 7x – 63 = 0
=>(x+9)(x-7) = 0
=> x = -9,7
II.y^2 – 15y + 56 = 0
=>y^2 – 7x – 8y + 56 = 0
=>(y -7)(y-8) = 0
=> y = 7,8
y>=x - I.4x^2 – 20x + 21 = 0
II.4y^2 = 4y + 15x>=yNo relation.y>xx>yy>=xOption B
I.4x^2 – 20x + 21 = 0
=>4x^2 – 14x – 6x + 21 = 0
=>(2x- 7)(2x – 3) = 0
=> x = 3/2,7/2
II.4y^2 = 4y + 15
=>4y^2 – 10y + 6y – 15 =0
=>(2y – 15)(2y+3) = 0
=>y = -3/2,5/2
No relation. - I.3x^2 +14x +15 = 0
II.2y^2 = 3y + 5y>=xx>=yx>yNo relation.y>xOption E
I.3x^2 +14x +15 = 0
=>3x^2 + 9x + 5x + 15 = 0
=>3x(x+3)+5(x+3) = 0
=>(3x+5)(x+3) =0
=>x = -5/3,-3
II.2y^2 = 3y + 5
=>2y^2 – 5y + 2y – 5 = 0
=>(y+1)(2y-5) = 0
=>y = -1,5/2
y>x - I.x^2 – 2x – 15 = 0
II.y^2 + 4y – 12 = 0x>=yy>=xx>yNo relation.y>xOption D
I.x^2 – 2x – 15 = 0
=>x^2 – 5x + 3x – 15 = 0
=>(x-5)(x+3) = 0
=> x = 5,-3
II.y^2 + 4y – 12 = 0
=>y^2 + 6y – 2y – 12 = 0
=>(y+6)(y-2) = 0
=>y = -6,2
No relation. - I.5x + 9y = 112
II.9x – 2y = 56x>yNo relation.y>=xx>=yy>xOption B
On solving both the equations, we get
x = y
No relation. - I.12x^2 – 31x + 20 = 0
II.10y^2 – 11y + 3 = 0x>yNo relation.x>=yy>=xy>xOption A
I.12x^2 – 31x + 20 = 0
=>12x^2 – 16x – 15x +20 = 0
=>(3x-4)(4x-5) = 0
=>x = 4/3,5/4
II.10y^2 – 11y + 3 = 0
=>10y^2 – 5y – 6y + 3 = 0
=>(5y-3)(2y-1) = 0
=>y = 3/5,1/2
x>y - I.x^2 + 31x + 234 = 0
II.y^2 – 2y – 195 = 0y>=xy>xx>yx>=yNo relation.Option A
I.x^2 + 31x + 234 = 0
=>x^2 + 18x + 13x + 234 = 0
=>(x+18)(x+13) = 0
=> x = -18,-13
II.y^2 – 2y – 195 = 0
=>y^2 – 15y + 13y – 195 = 0
=>(y-15)(y+13) = 0
=>y = 15,-13
y>=x - I.x + 20(x)^1/2 + 96 = 0
II.y – 4(y)^1/2 – 140 = 0No relation.y>xy>=xx>yx>=yOption A
I.x + 20(x)^1/2 + 96 = 0
=>(x^2)^1/2 + 20(x)^1/2 + 96 = 0
=>(x^2)^1/2 + 12(x)^1/2 + 8(x)^1/2 + 96 = 0
=>[(x)^1/2 + 12][(x)^1/2 + 8] = 0
=>x = 144,64
II.y – 4(y)^1/2 – 140 = 0
=>(y^2)^1/2 – 4(y)^1/2 – 140 = 0
=>(y^2)^1/2 – 14(y)^1/2 + 10(y)^1/2 – 140 = 0
=>[(y)^1/2 – 14][(y)^1/2 + 10] = 0
=> y = 100,196
No relation. - I.x^2 + 9(3)^1/2x + 54 = 0
II.y^2 + [11 + 7(3)^1/2]y + 77(3)^1/2 = 0x>=yNo relation.y>xy>=xx>yOption E
I.x^2 + 9(3)^1/2x + 54 = 0
=>x^2 + 6(3)^1/2x + 3(3)^1/2x + 54 = 0
=>[x+6(3)^1/2][x+3(3)^1/2] = 0
=>x = -6(3)^1/2,-3(3)^1/2
II.y^2 + [11 + 7(3)^1/2]y + 77(3)^1/2 = 0
=>y^2 + 11y + 7(3)^1/2y + 77(3)^1/2 = 0
=>(y+11)[y+7(3)^1/2] = 0
=>y = -11,-7(3)^1/2
x>y - I.x^2 – 3x – 54 = 0
II.y^2 – 19y + 90 = 0x>yy>xy>=xNo relation.x>=yOption C
I.x^2 – 3x – 54 = 0
=>x^2 – 9x + 6x – 54 = 0
=>(x-9)(x+6) = 0
=>x = 9,-6
II.y^2 – 19y + 90 = 0
=>y^2 – 9y – 10y + 90 = 0
=>(y-9)(y-10) = 0
=>y = 9,10
y>=x